First assessment of biomarker responses and contaminant levels in Balaenoptera edeni skin biopsies of Gulf of California (Mexico). - FOSSI, MARIA CRISTINA; CASINI, SILVIA; MARSILI, LETIZIA; Urban J.; Maltese S.; Mazzi L.; Coppola D.; Panigada S.; Lauriano G.; Niño C.; Rojas Bracho L. (2010)
The main objective of this project was to apply, for the first time, a suite of sensitive non-lethal biomarkers in skin biopsy of the mysticete unexplored species Bryde’s whale (Balaenoptera edeni) to evaluate the toxicological status of this cetacean species in the Gulf of California. In this species we developed a “multitrial- biomarker-tool”, combining protein biomarkers (western blot of CYP1A1, CYP2B) with analysis of OCs and PAHs. In this paper we also explored the level and effects of OCs and PAHs in skin biopsies of fin whale (Balaenoptera physalus) populations of the Gulf of California and the heavy polluted areas of the Mediterranean Sea.